Pharmacovigilance system in Eurasian Economic Union - I. L. Asetskaya; S. K. Zyryanov; A. S. Kolbin; D. Yu. Belousov (Izdatelstvo OKI, 2019)
The article deals with the main provisions of the basic document - «Rules of good practice of pharmacovigilance of the Eurasian economic Union», which regulates the study and prevention of adverse reactions and other problems associated with drugs in the member States of the Union, including the Russian Federation. Also, the Rules establish requirements for the organization of pharmacovigilance system in pharmaceutical companies, detail the work of manufacturers in the field of risk management, as well as determine the procedure for informing employees of the pharmaceutical industry and specialists of medical institutions of the authorized bodies about the identified safety problems in the use of medicines.